2018
DOI: 10.1111/ppc.12289
|View full text |Cite
|
Sign up to set email alerts
|

The views and habits of the individuals with mental illness about physical activity and nutrition

Abstract: Mental health nurses should be aware of the barriers of individuals with mental illness. It is recommended that mental health nurses make interventions to encourage patients to have physical activity and healthy eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…Some consumers who enthusiastically engaged in health behaviour changes experienced physical and mental barriers such as negative symptoms of mental illness and adverse effects from psychiatric medications. Previous literature confirms these perceived barriers impede the social, occupational and physical functioning of consumers (Department of Health 2017; Hassan et al 2020;Hemmings & Soundy 2020;Ince & G€ un€ us ßen 2018;Morgan et al 2014). Consumers in the current study reported the PHNC was able to expertly navigate these challenges by exhibiting sensitivity to these barriers whilst working with the consumer to adopt alternative strategies for achieving their personal health goal.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Some consumers who enthusiastically engaged in health behaviour changes experienced physical and mental barriers such as negative symptoms of mental illness and adverse effects from psychiatric medications. Previous literature confirms these perceived barriers impede the social, occupational and physical functioning of consumers (Department of Health 2017; Hassan et al 2020;Hemmings & Soundy 2020;Ince & G€ un€ us ßen 2018;Morgan et al 2014). Consumers in the current study reported the PHNC was able to expertly navigate these challenges by exhibiting sensitivity to these barriers whilst working with the consumer to adopt alternative strategies for achieving their personal health goal.…”
Section: Discussionsupporting
confidence: 66%
“…Previous literature confirms these perceived barriers impede the social, occupational and physical functioning of consumers (Department of Health 2017; Hassan et al . 2020; Hemmings & Soundy 2020; Ince & Günüşen 2018; Morgan et al . 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These barriers were related to disease symptoms such as not wanting to leave home due to the side effects of psychiatric drugs, laziness, and pain. In a study conducted by Çelik Ince et al examining individuals with severe mental illness in Turkey, the authors determined that the patients' lack of desire, laziness, rapid fatigue, lack of energy, and a lack of motivation prevented them from being physically active. In a qualitative study by Happell et al that investigated the caregivers of individuals with severe mental illness in Australia, caregivers stated that their patients experienced difficulty performing or maintaining physical activities because of the side effects of drugs, a preference to stay at home rather than participating in social activities, and a lack of motivation and energy.…”
Section: Discussionmentioning
confidence: 99%
“…Among psychiatric patients, 30%‐40% of deaths are caused by suicides and injuries while 60% are attributed to physical diseases that affect the cardiovascular and respiratory systems, infectious diseases and diabetes . The causes of physical health problems have been reported and include weight gain, psychotropic drug‐related causes, such as sedation, unhealthy lifestyle habits (smoking, alcohol, and a sedentary life), mental health related symptoms, and depressive mood states . Another explanation for the negative health outcomes of these individuals stems from their inability to sufficiently benefit from social health services compared with the general population.…”
Section: Introductionmentioning
confidence: 99%